1275PSafety and clinical activity of subcutaneously (SC) administered anti-PD-1 antibody PF-06801591 in phase I dose-expansion cohorts of locally advanced or metastatic non-small cell lung cancer (NSCLC) and urothelial carcinoma (UC). (1st October 2019) - Cho, B C; Penkov, K; Bondarenko, I; Korozan, M; Kurochkin, A; Pikiel, J; Kulyaba, Y; Ahn, H K; Odintsova, S; Davda, J; Forgie, A; Wang, X; et al.
Abstract: Background: The first-in-human, ongoing phase I study of PF-06801591, a humanized IgG4 antibody to programmed cell death 1 (PD-1) receptor, consisted of a Part 1 dose escalation and Part 2 dose expansion. In Part 1, PF-06801591 was administered intravenously or SC with an acceptable safety profile and antitumor activity in several solid tumor types. Herein, we report on Part 2 where we further evaluated SC PF-06801591 in patients (pts) with NSCLC and UC. Methods: Anti-PD-1/L1-naïve pts with NSCLC (n = 68) and UC (n = 38) received SC PF-06801591 300 mg q4w. NSCLC pts had ≤1 prior line of chemotherapy (CT) ± ≥1 ALK/EGFR mutation-directed therapies (if applicable) and UC pts had ≤2 lines of prior CT. Tumors were evaluated q8w by RECIST 1.1. Blood samples were collected for pharmacokinetic (PK) and immunogenicity assessments. Archival or baseline biopsies were evaluated by immunohistochemistry for PD-L1, RNA-seq, and whole exome sequencing. Results: As of 27Dec2018, with median duration of treatment of 2.8 mos. in all 106 treated pts (55 still receiving treatment), 50.9% had treatment-related AEs (TRAEs) with 8.5% grade 3 or higher. Most common TRAEs were hyperthyroidism (9.4%), pruritus (6.6%), and increased amylase/lipase, anemia, hypothyroidism, pneumonitis, and rash (4.7% each). Treatment-emergent anti-drug antibodies were detected in 3 pts. With median follow-up of 5.1 mos. in 67 modified intent to treat (mITT) NSCLC pts, 11 (16.4%) pts achieved a partial response (PR) and 26 (38.8%) had stable disease (SD); the objective response rate (ORR) was 16.4% with 95% confidence interval (CI) 8.5-27.5% (25% in pts with ≥1% tumor cell PD-L1 expression). With median follow-up of 3.0 mos. in 37 mITT UC pts, 6 (16.2%) pts had a PR and 13 (35.1%) had SD; ORR was 16.2% (95% CI 6.2-32.0%). PK and biomarker data will be presented. Conclusions: SC PF-06801591 given monthly was well tolerated, with minimal rates of injection site reactions and low incidence of immunogenicity. SC PF-06801591 demonstrated antitumor activity in NSCLC and UC pts at an early time point. The study is ongoing to further assess the durability of responses and long-term safety profile. Clinical trial identification: NCT02573259. Editorial acknowledgement: S. Mariani MD PhD of Engage Scientific Solutions, Southport, CT, funded by Pfizer and L. Chen. Legal entity responsible for the study: Pfizer Inc. Funding: Pfizer Inc. Disclosure: B.C. Cho: Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): MOGAM Institute; Research grant / Funding (institution): Dong-A ST; Research grant / Funding (institution), Licensing / Royalties: Champions Oncology; Advisory / Consultancy, Research grant / Funding (institution): Janssen; Advisory / Consultancy, Research grant / Funding (institution): Yuhan; Advisory / Consultancy, Research grant / Funding (institution): Ono; Research grant / Funding (institution): Dizal Pharma; Advisory / Consultancy, Research grant / Funding (institution): MSD; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: Roche; Advisory / Consultancy: BMS; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Eli Lilly; Advisory / Consultancy: Takeda; Shareholder / Stockholder / Stock options: TheraCanVac Inc; Shareholder / Stockholder / Stock options: Gencurix Inc; Shareholder / Stockholder / Stock options: Bridgebio Therapeutics. K. Penkov: Research grant / Funding (institution): AbbVie; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): MSD; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Prestige Biopharma; Research grant / Funding (institution): Regeneron; Research grant / Funding (institution): Tanvex. M. Korozan: Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Genentech/Roche; Research grant / Funding (institution): Regeneron. Y. Kulyaba: Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Azaya Therapeutics; Research grant / Funding (institution): Celltrion; Research grant / Funding (institution): GlaxoSmithKline; Research grant / Funding (institution): Janssen; Research grant / Funding (institution): Merck; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Regeneron; Research grant / Funding (institution): Roche; Research grant / Funding (institution): Synta Pharmaceuticals; Research grant / Funding (institution): Tanvex. H.K. Ahn: Honoraria (self): AstraZeneca; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Eisai; Honoraria (self): Ono; Honoraria (self): Roche. S. Odintsova: Full / Part-time employment: Complete Medical Technologies. J. Davda: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer. A. Forgie: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer. X. Wang: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer. R. Li: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer. I.A. Jacobs: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer. F. Kazazi: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer. J. Chou: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer. M.L. Johnson: Honoraria (institution), Research grant / Funding (institution): AstraZeneca; Honoraria (institution), Research grant / Funding (institution): Genentech/Roche; Honoraria (institution), Research grant / Funding (institution): Boehringer Ingelheim; Honoraria (institution), Research grant / Funding (institution): Loxo; Honoraria (institution), Research grant / Funding (institution): Merck; Honoraria (institution), Research grant / Funding (institution): Mirati; Honoraria (institution), Research grant / Funding (institution): Sanofi; Honoraria (institution): Calithera; Honoraria (institution): Celgene; Research grant / Funding (institution): Lilly; Research grant / Funding (institution): EMD Serono; Research grant / Funding (institution): Janssen; Research grant / Funding (institution): GenMab; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): AbbVie; Research grant / Funding (institution): StemCentrix; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Incyte; Research grant / Funding (institution): Array BioPharma; Research grant / Funding (institution): Regeneron; Research grant / Funding (institution): Adaptimmune; Research grant / Funding (institution): Amgen; Research grant / Funding (institution): Apexigen; Research grant / Funding (institution): BeiGene; Research grant / Funding (institution): BerGenBio; Research grant / Funding (institution): Birdie; Research grant / Funding (institution): Checkpoint Therapeutics; Research grant / Funding (institution): Corvus; Research grant / Funding (institution): Cytomx; Research grant / Funding (institution): Daiichi–Sankyo; Research grant / Funding (institution): Dynavax; Research grant / Funding (institution): G1 Therapeutics; Research grant / Funding (institution): Genocea; Research grant / Funding (institution): Gritstone; Research grant / Funding (institution): Hengrui Therapeutics; Research grant / Funding (institution): Lycera; Research grant / Funding (institution): Neovia; Research grant / Funding (institution): Syndax; Research grant / Funding (institution): Tarveda; Spouse / Financial dependant, contract lobbyist : Astellas; Spouse / Financial dependant, contract lobbyist : Otsuka Pharmaceuticals. All other authors have declared no conflicts of interest.